Atrio-ventricular kinetics in patients with coronary heart disease and atrial fibrillation - N. S. Volkova; L. I. Kuznetsova; E. V. Parkhonyuk; Yu. G. Shwarts (Кардиоваскулярная терапия и профилактика)
Aim. To investigate myocardial kinetics in atrio-ventricular junction (AVJ) area among patients with persistent atrial fibrillation (PAF).Material and methods. The main group included 34 patients with PAF, the comparison group - 20 patients with coronary heart disease (CHD) without myocardial infarction or arrhythmias in anamnesis, the control group -20 healthy people. General clinical examination and Doppler tissue imaging (DTI) echocardiography were performed. The difference in velocity of lower interatrial septum segment and upper interventricular septum segment (asynchronism) along longitudinal cardial axis in various cardiac cycle phases was studied. Univariate dispersion and non-parametric correlation methods were used for statistical analysis.Results. Asynchronism severity was weakly related to standard parameters of systolic and diastolic myocardial function. In CHD patients, regardless of arrhythmia type, asynchronism was significantly less manifested during ventricular isovolumic relaxation (+ and - waves) and passive filling periods, comparing to healthy individuals. Similar tendencies were observed for other cardiac cycle phases. In patients with CHD and PAF, asynchronism was even less manifested, observed mainly in pre-ejection and ejection periods.Conclusion. The results obtained reflected morphologically verified fibrosis, typical for PAF, and demonstrated satisfactory diagnostic potential of DTI method.